SERAPAH DALAM MASYARAKAT MELAYU KAMPUNG SAIGON KOTA PONTIANAK - Kurniawan, Syamsul (UIN Sunan Kalijaga Yogyakarta, 2013)
Serapah for the Malay people of Kampung Saigon, Pontianak, is believed to have magical powers with several purposes such as to protect themselves and property, weaken the enemy, conquer women and so forth. This study therefore aims to describe the actual prac- tice of Serapah spell as observed by the Malay of Kampung Saigon. In reality, animism and dynamism have contributed to a strong conviction about the efficacy of Serapah in the everyday life of Malay people of Kampung Saigon. Such a conviction in turn allows oral development ofÂ Serapah from one generation to another. Serapah as practice of incantations which are growing in this place, not only shows an old cultural phenomenon alive today, but also displays a form of religious expression in the Malay community. There is even a provision that the Serapah must be started with reading Basmallah (Bismillah) and closed with the phrase â€œBerkat doa Laailahaillallah Muhammadar rasulullahâ€.